Caracterización agromorfológica de 80 accesiones de maíz (zea mays) del banco de germoplasma de la Universidad Tecnica de Cotopaxi en el centro experimental agropecuario Salache alto ceasa utc - Morales Fernández, Guillermo Rubén (2016)
This research was conducted at the Academic Unit - CAREN Technical University of Cotopaxi, with the theme: Characterization agromorphological 80 accessions of maize (Zea mays) genebank of the Technical University of Cotopaxi in the Agricultural Experimental Center High Salache CEASA UTC, in which 19 29 quantitative and qualitative variables were evaluated. Whose specific objectives were to evaluate morphologically 80 accessions of corn. Form groups of units associated with the degree of genetic similarity. To identify the most outstanding accessions according to requirements of farmers. With the results obtained in the characterization phase, a distance matrix is settle through Euclidean weighting coefficient by a dendrogram….